"Shared and Collective Stress": 2SLGBTQI and Allied Mental Healthcare Providers' Experiences and Challenges During COVID-19 in Canada - Kimberly Seida; Félix Desmeules-Trudel; Brittany A. E. Jakubiec (Atlantis)
The confluence of increased demand for mental health services and decreased resources due to the COVID-19 pandemic has created multiple challenges for mental healthcare and social service providers. 2SLGBTQI service providers may be disproportionately impacted by pandemic-related challenges, such as psychological distress, vicarious traumatization, and burnout. However, there are significant knowledge gaps regarding the needs and experiences of 2SLGBTQI and allied service providers in the context of the COVID-19 pandemic in Canada. To address these gaps, we conducted a national survey (N = 304), eight semi-structured focus groups, and five semi-structured interviews (N = 61) with 2SLGBTQI care seekers and service providers across Canada. Based on data from the 106 2SLGBTQI service providers and 3 allied service providers who took part in these research activities, this paper explores the challenges service providers encounter when providing care to 2SLGBTQI individuals as well as their adaptive responses to these challenges. Understanding the experiences of service providers who share lived experiences of discrimination and marginalization with their clients is critical to addressing barriers to affirming mental healthcare, shifting services to meet the evolving needs of both care seekers and providers, and developing upstream, comprehensive solutions to address the causes of 2SLGBTQI mental health disparities.